Applying Artificial Intelligence (AI) to High School Vietnamese Language Arts - Thi Thu Hien, Pham (VNU Journal of Science: Education Research, 2026)
In the current teaching of Vietnamese Language Arts at high schools in Vietnam, the application of artificial intelligence (AI) tools is both inevitable and essential. However, to date, there has been no comprehensive or specific research in Vietnam guiding how to apply AI in teaching reading comprehension, writing, speaking and listening, and Vietnamese language practice in accordance with the requirements of the 2018 Vietnamese Language Arts curriculum. By employing methods of document analysis, synthesis, and experimentation, the author proposes practical ways to integrate currently popular AI tools, such as ChatGPT, Gemini, etc., into teaching high school Vietnamese Language Arts. These proposals aim to assist students in reading comprehension, writing, speaking and listening, and Vietnamese language practice through structured processes, thereby meeting lesson objectives, making classes more vivid, engaging, and modern, and ultimately developing learners' qualities and competencies. These recommendations also contribute to implementing the digital transformation policy, aimed at enhancing the quality of education in general and the teaching of Vietnamese Language Arts in high schools in particular.